Peningkatan Minat Anak Sekolah Minggu Usia 9-12 Tahun Dalam Mengikuti Ibadah Minggu Di Gereja Protestan Persekutuan (GPP) Parhorboan Resort Tapanuli Utara II Melalui Penggunaan Media Audio Visual - Sophia Gabriella Br Manik; Jungjungan Simorangkir; Robert Juni Tua Sitio (Lumen: Jurnal Pendidikan Agama Katekese dan Pastoral, 2023)
Sunday school learning which initially used the lecture method, now there are various churches that use various teaching methods, one of which is audio-visual media. The problem, according to the author's observations, especially at the Fellowship Protestant Church (GPP) Parhorboan Resort Tapanuli Utara II, is that school teachers are still lacking in using teaching methods that can create interaction between teachers and children, thus having an impact on children's interest in participating in Sunday school worship. The research method used in this research is a descriptive qualitative method. The research implementation uses procedures that produce descriptive data in the form of written and spoken words from people whose behavior is observed through interviews or observations using a qualitative approach. This research aims to find out how to increase the interest of Sunday school children aged 9-12 years in attending Sunday services at the Fellowship Protestant Church (GPP) Parhorboan Resort Tapanuli Utara II through the use of audio-visual media. The results of this research show that Sunday school children receiving teaching delivered by Sunday school teachers using audio-visual media can increase Sunday school children's interest in attending worship.